2016
DOI: 10.1097/psn.0000000000000134
|View full text |Cite
|
Sign up to set email alerts
|

Vibration for Pain Reduction in a Plastic Surgery Clinic

Abstract: Patients can experience significant pain during routine procedures in the plastic surgery clinic. Methods for clinical pain reduction are often impractical, time-consuming, or ineffective. Vibration is a safe, inexpensive, and highly applicable modality for pain reduction that can be readily utilized for a wide variety of procedures. This study evaluated the use of vibration as a viable pain-reduction strategy in the clinical plastic surgery setting. Patients requiring at least 2 consecutive procedures that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…8 The application of a vibratory stimulus has been shown to improve patient discomfort associated with cosmetic botulinum toxin injections. 6,9 The ''gate-control'' theory, initially proposed in 1965, suggests that intensity of pain can be mitigated by concurrent non-noxious stimulation. 10,11 Studies have applied this theory to eyelid local anesthesia injections, 12 dermal filler injections, 13 and keloid steroid injections 14 with reduction in pain outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…8 The application of a vibratory stimulus has been shown to improve patient discomfort associated with cosmetic botulinum toxin injections. 6,9 The ''gate-control'' theory, initially proposed in 1965, suggests that intensity of pain can be mitigated by concurrent non-noxious stimulation. 10,11 Studies have applied this theory to eyelid local anesthesia injections, 12 dermal filler injections, 13 and keloid steroid injections 14 with reduction in pain outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Vibration has been previously shown to significantly decrease pain perceived by patients in multiple clinical settings, but, to our knowledge, had not been tested in those who catastrophize pain. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] In our study, we found that patients who catastrophized pain experience a minimum clinically difference in relative change (≥22%) and patients who did not catastrophize pain experience a substantial clinically important difference (≥57%) with the use of vibration during anesthetic injection (Table 3). 39 During multivariate analysis of the entire cohort, the only variable to significantly affect the perceived pain of patients during anesthetic injection was the presence of the VAD (F statistic, 2.741; P = .03) (eTable in Supplement 2).…”
Section: Discussionmentioning
confidence: 86%
“…The use of nonnoxious tactile stimulation, specifically vibration, has been shown to significantly decrease pain perceived by patients in many clinical settings . Generalizability of these previous studies are limited owing to small sample size, the use of volunteers, and unreported and/or unperformed participant training for accurate pain score reporting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 Furthermore, many small cohort studies found that age was not a factor in patient response to vibration analgesia. 17,24,44 In the intraoperative MMS setting, younger patients are more likely to report pain. 3 However, postoperatively, there are conflicting findings; Limthongkul and colleagues showed no correlation between age and pain, whereas Firoz and colleagues reported increased pain in younger patients.…”
Section: Discussionmentioning
confidence: 99%